Changes in soil chemical properties under two contrasting plantation systems on the Zululand coastal plain, South Africa - Noble, A.D.; Berthelsen, S.; Mather, J. (2005)
Over the past 4 decades there has been considerable expansion in the plantation forestry along the eastern seaboard of South Africa. In particular there have been significant increases in eucalypt, and to a less extent, pine plantations on soils of a light sandy texture along the Zululand coastal plain. These soils are characteristically dominated by sands with low clay and organic matter contents, have low cation exchange capacity and water holding capacity. Pedogenesis and selected chemical attributes of a 49-year-old stand of Eucalyptus grandis and Pinus elliottii established on these sands were compared. Changes in soil pH, exchangeable cations, organic carbon, extractable Fe and Al and the surface charge characteristics were investigated. Evidence of the development of bleached A2e horizon within the surface 0-5 cm depth interval under E. grandis was confirmed through the development of surface charge fingerprints, changes in organic carbon and Fe and Al mobilization for each of the pedogenetically distinct horizons. Such development was not observed under the P. elliottii stand, suggesting that this pine species has had less impact on the soil. It is argued that the rate of A2e horizon development is not dissimilar to that observed under native forest ecosystems in Australia, although considerably slower that those observed under reclaimed sand mining operations. Whilst these systems appear to be relatively stable due to no clear felling and timber product extraction, this could drastically change with the introduction of short-term rotations of fast growing clonal plantations, questioning the long-term sustainability of these production systems on these light textured sands.